Numerical analysis of shear transfer across an initially uncrack reinforced concrete member. (1st November 2015) - Xu, Juechun; Wu, Chengqing; Li, Zhong-Xian; Ng, Ching-Tai
Highlights: Finite element modeling of shear transfer behavior in initially uncracked reinforced concrete members. Finite element models are calibrated using experimental push-off tests. Parametric study on evaluating the characteristics between the shear stress and slip for a range of design parameters. Derivation equations for evaluating the ultimate shear stress and relationship of shear stress to slip relationship. Abstract: An investigation of shear transfer behavior in initially uncracked reinforced concrete members is conducted using finite element modeling method in this study. Although earlier experimental studies have been carried out to identify the role of different design parameters on the ultimate shear strength, there are no design provisions that are available to predict the relationship of shear stress to slip as a function of the basic parameters. One of the aims of this paper is to improve insight into the characteristics between the shear stress and slip for a range of design parameters, such as concrete strength, percentage of dowel and variation of lateral normal pressure on RC members. The other aim of this paper is to derive a set of simplified equations for evaluating the ultimate shear stress and relationship of shear stress to slip in practical structural design. High-fidelity finite element models are developed using LS-DYNA program to simulate push-off tests, and the models are calibrated using experimental results. Parametric studies are then carried out to generate data with the consideration of different combinations of the structural design parameters, i.e., concrete strength, percentage of dowel steel and lateral normal pressures. It is found that the numerical models are accurate in predicting the interface shear strength and slip occurring along the shear plane of the push-off test specimens. The study also shows that there is a good agreement in predicting the shear stress to slip relationship between the results calculated by simplified equations and numerical models, and experimental results.